2018
DOI: 10.5812/ijhrba.67788
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interactive Multimedia Education on Knowledge and Attitude of High School Teachers About Prevention of Health-Risk Behaviors

Abstract: Background: Health risk behaviors among teenagers are common and schools considered as an ideal place for conducting preventions programs. Objectives: The current study aimed at determining the effect of interactive multimedia on knowledge and attitudes of high school teachers regarding prevention of students' health-risk behaviors. Patients and Methods: A total of 150 high school teachers were randomly assigned to intervention and control groups. Data were collected using a written test on knowledge and a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This study showed similar results with the studies mentioned above, in those studies conducted in Taiwan and overseas, multimedia learning could improve knowledge, attitude, and behavioral intention [ 24 , 28 , 29 ]. However, Lahti, Hätönen, and Välimäki (2014) had a different finding in their systematic review study; there were 2491 nurses and nursing students were enrolled.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study showed similar results with the studies mentioned above, in those studies conducted in Taiwan and overseas, multimedia learning could improve knowledge, attitude, and behavioral intention [ 24 , 28 , 29 ]. However, Lahti, Hätönen, and Välimäki (2014) had a different finding in their systematic review study; there were 2491 nurses and nursing students were enrolled.…”
Section: Discussionsupporting
confidence: 89%
“…The study results revealed that the students who received lectures in a digital model had significantly better outcomes in knowledge acquirement, attitude, and satisfaction than those who received lectures in classrooms [27]. Momennasab et al (2018) investigated the effect of digital-based learning on the knowledge and attitude of 150 high school teachers about the prevention of health-risk behaviors in students. The result showed that both multimedia and booklets could enhance the teachers' knowledge and improve their attitudes toward the prevention of health-risk behaviors [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Fary et al indicated that both of these educational methods led to better learning among physiotherapy students [12]. Momennasab et al compared the effects of booklet and multimedia methods on teachers' knowledge on preventing high-risk behaviors and reported that both approaches could affect teachers' knowledge [13].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have been conducted to compare the multimedia and conventional methods such as booklets and indicated that multimedia plays a more signi cant effect than conventional education on knowledge, skill, and self-e cacy [12], depression and anxiety [13], the severity of pain, overdramatization of pain, and coping with pain [14], as well as knowledge and skills among the patients [15].…”
mentioning
confidence: 99%